Deep Foundation Ground Anchors In The Wind Energy Industry - Current Status Of Design And Construction Practices And Introduction Of A Patented System To Improve Foundation Performance - Josef K. Alter (Deep Foundations Institute, 2010)
Long-term performance and behavior of post-tensioned ground anchors subjected to axial cyclic loading constitutes an important aspect of the stability, reliability and overall performance of wind turbine deep foundations. Axial cyclic loading of post-tensioned (PT) ground anchors in soils has not been thoroughly investigated as evidenced by the research conducted for this topic. This paper evaluates research test data, available literature, and industry expert opinion on the current status and problems of deep foundation post-tensioned ground anchor (PTGA) technology, as applicable to the wind energy industry. It also introduces a proposed design solution that addresses the problems of construction cost and long-term performance of wind turbine deep foundations in soils subjected to dynamic cyclic axial loading. Deep foundations using ground anchors for wind turbines have only recently gained attention as a possible viable alternative to the mass spread footings currently in use. One of the primary problems with general acceptance of current PTGA designs is the need for long-term anchor maintenance. The research that was conducted for this study indicates that current literature only partially addresses the many factors influencing load capacity and pullout performance of ground anchors. The lack of information indicates the deep foundation industry has fallen behind in designing and implementing new technology to improve safety and performance, ensure sustainability, reduce costs, and address environmental responsibility. This paper describes the significance of this problem as it applies to the wind energy market, and proposes a new technology solution. The research, expert opinion, and analysis presented by the author is used to support the premise that ground anchor construction cost and long-term maintenance can be reduced with PTGA systems using the Con-Tech Systems (CTS) patent-pending Groutable Void Form (GVF) technology.